Radical inclusion: Students with disabilities’ professional learning in South African higher learning - Ndlovu, S. (South African Journal of Higher Education, 2020)
Abstract Inclusion of all in learning and workplace spaces has continued to be an urgent agenda for democratic governments and relevant stakeholders in higher learning, globally and in South Africa particularly. However, whilst the focus is on this, the original idea of inclusion has been lost, resulting in different versions which stakeholders ‘tick off” as meaning inclusion. By virtue of a misconstrued idea of inclusion, students with disabilities in higher learning contexts are individually accommodated rather than included. This empirical paper isolates what the key stakeholders supporting disability at a specific institution of higher learning in South Africa, consider as inclusion and how students with disabilities are fitted into the system, rather than a total institutional transformation, in which all students are included in their diversities. The paper recommends a radical inclusion as a re-invention that can recapture the original idea and discourse of inclusion which has been lost.